Competitiveness of industrial companies in Kazakhstan in the context of ESG transformation - Maryana Valerievna Uspanova; Zaure Abildinovna Salzhanova (World Scientific Reports, 2023)
The article discusses the ESG-principles of economic development, which fully meet the concept of sustainable development. The key indicators of modern entrepreneurship are a responsible attitude to the environment (E-criterion), compliance with the social responsibility of business (S-criterion), and high-quality company management (G-criterion). Many enterprises from various industries already share ESG principles and actively use them in their activities. International rating agencies develop ESG ratings of companies that show the degree of commitment of enterprises to these principles. Kazakhstani agencies also form ESG ratings for domestic companies. However, not all companies report to ESG yet. In addition, the issue of environmental problems is acute. The article identifies the reasons that will contribute to the active ESG transformation of industrial enterprises, including changes in the policy of providing responsible investments mainly to companies with a high ESG rating, ensuring the competitiveness and attractiveness of Kazakhstani industrial enterprises in the global service market. It is emphasized that the results of the implementation of the ESG strategy by enterprises of the industrial complex become the basis for the preparation of public non-financial ESG reporting, which in turn determines its place in the ESG rating and increases the level of competitiveness.